2018
DOI: 10.17221/430/2018-pse
|View full text |Cite
|
Sign up to set email alerts
|

The effect of genotype, weather conditions and cropping system on antioxidant activity and content of selected antioxidant compounds in wheat with coloured grain

Abstract: The aim of the study was to evaluate total antioxidant activity (TAA) and total content of carotenoids (TCC), anthocyanins (TAC), phenolics (TPC) and phenolic acids (PAs) in grain of selected pigmented wheat genotypes and traditional control cultivar cultivated under organic and conventional cropping systems in two-year trials. All of the evaluated parameters were significantly affected both by genotype and evaluated environmental factors. While in TPC, PAs and TCC the effect of years prevailed, TAC was affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 23 publications
2
17
0
1
Order By: Relevance
“…Investigation of the effects of cropping systems on the content of different phytochemicals was the aim of many studies. Most of them agree with the conclusion that crops from organic farming usually contain higher concentrations of antioxidant compounds compared to crops cultivated conventionally (Zuchowski et al 2011, Barański et al 2014, Zrcková et al 2018. One of the reasons is probably the fact that in organic farming Table 4.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…Investigation of the effects of cropping systems on the content of different phytochemicals was the aim of many studies. Most of them agree with the conclusion that crops from organic farming usually contain higher concentrations of antioxidant compounds compared to crops cultivated conventionally (Zuchowski et al 2011, Barański et al 2014, Zrcková et al 2018. One of the reasons is probably the fact that in organic farming Table 4.…”
Section: Resultssupporting
confidence: 68%
“…Nevertheless, in 2019, when the content of most of the evaluated antioxidant compounds was higher, oat cultivars were exposed to higher temperatures and lower precipitation compared to 2018. It is already known that plants increase the synthesis of many antioxidants in stress conditions, including abiotic stresses like drought and/or heat stress (Ficco et al 2014, Ben Halima et al 2015, Zrcková et al 2018. However, in view of the fact that the differences in weather conditions between both evaluated years were not too high, we would expect that differences in the content of evaluated antioxidants would be lower.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…In agreement to our results, Costanzo et al [36] found that tillage system had no significant effect on antioxidants capacity of wheat. In contrast, many results reported that antioxidants capacity depends on many factors such environment, genotype, management practices and their interactions, in addition to the applied test and the extraction solvents [37][38]. Huseynova [39] reported that under stress conditions, an increase of antioxidants concentration is observed and antioxidants play a determinant role to protect plant against oxidative stress.…”
Section: Antioxidant Capacity (Dpph)mentioning
confidence: 99%
“…Four colored winter wheat cultivars along with two checks were studied for two years under organic and non-organic cropping systems [27]. While total phenolic content was more affected by year, anthocyanin content was more affected by genotype and the effect of environment and genotype was comparable for total antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%